The association between early marriage and mental disorder among young migrant and non-migrant women: a Norwegian register-based study - Kamila Angelika Hynek; Dawit Shawel Abebe; Aart C. Liefbroer; Lars Johan Hauge; Melanie Lindsay Straiton (BMC, 2022)
Abstract Background Marriage is considered beneficial for mental health when stable and of high quality. Yet, it is unclear whether marriage is equally advantageous for everyone regardless of marital timing or migrant background. This study aimed to investigate the association between early marriage and mental disorder, defined by outpatient mental healthcare (OPMH) service use, and whether the association varies between migrant and non-migrant women. Methods Using data from four Norwegian national registers, we applied discrete-time logistic regression analyses to study the aims of interest, among 602 473 young women aged 17-35 years. All women were followed from 2006 or the year they turned 17, and until first OPMH consultation, 2015 (study end), the year they turned 35, when emigrated, died, or changed marital status from married to separated, divorced, or widowed. Results Results show that unmarried and early married women had increased odds of mental disorder when compared to on-time married women. However, the differences between the early and on-time married women were explained by differences in educational level. There was no significant interaction between marital status and migrant background. Conclusions Differences in mental health between early- and on time married women are attributed to poorer educational attainment of women who marry early. Furthermore, migrant background seems to have a limited role in the association between marital timing and mental disorder. The promotion of formal education among young women could contribute to the accumulation of socioeconomic and psychosocial resources, thus, reducing the risk of mental disorder, also among early married women.